Conserving livestock genetic resources for people - International Livestock Research Institute (International Livestock Research Institute, 2007)
People and domesticated animals have relied on each other for thousands of years. But modern life is wiping out ancient breeds. New approaches are needed to ensure the survival of these vital animal genetic resources.